MUSIK TERAPI DALAM PERSPEKTIF BUDAYA - Dahlan Taher (Imaji, 2006)
Classical music is said to have healing power. However, whether it can be used universally as common medicines remains questionable. The fact shows how music perceived by human senses is the same among people of different cultures. On the other hand, since music is a product of culture, human perception of music might also vary according to their cultures. Some people have high appreciation towards music so that they can appreciate various cultures while the others do not. Therefore, the use of therapeutic music should be in accordance with someone’s sense of appreciation towards it so that the therapy can give better effects. Keywords: classical music, therapy, culture